2020
DOI: 10.1093/biolre/ioz233
|View full text |Cite
|
Sign up to set email alerts
|

Uterine epithelial expression of the tumor necrosis factor superfamily: a strategy for immune privilege during pregnancy in a true epitheliochorial placentation species

Abstract: The maternal immune system tolerates semi-allogeneic placental tissues during pregnancy. Fas ligand (FASLG) and tumor necrosis factor superfamily 10 (TNFSF10) are known to be components of maternal immune tolerance in humans and mice. However, the role of FASLG and TNFSF10 in the tolerance process has not been studied in pigs, which form a true epitheliochorial type placenta. Thus, the present study examined the expression and function of FASLG and TNFSF10 and their receptors at the maternal-conceptus interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The endometrial TNFSF10 could target the conceptus via uEVs. Based on the proposed functions in other species, this gene could also play a role in establishing an immune privileged environment at the maternal‐embryo interface in the mare 96 …”
Section: Discussionmentioning
confidence: 99%
“…The endometrial TNFSF10 could target the conceptus via uEVs. Based on the proposed functions in other species, this gene could also play a role in establishing an immune privileged environment at the maternal‐embryo interface in the mare 96 …”
Section: Discussionmentioning
confidence: 99%
“…In non-primate species, menstruation does not occur as part of the estrous cycle, but apoptosis is nonetheless involved in endometrial remodeling during cyclical cell proliferation and degeneration. In mice, apoptosis in the uterine tissue is regulated by ovarian steroid hormones during the estrous cycle and occurs in the decidua after implantation [4][5][6] In pigs, apoptotic cells have been detected in the endometrium during the estrous cycle and pregnancy, mostly in the stroma at the time of implantation [7,8]. Our previous study in pigs showed that a large number of maternal T cells is recruited into the endometrium during the implantation period [9], and some T cells expressing cell death receptors undergo apoptosis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Pig conceptus interferons are not believed to have an antiluteolytic effect but rather paracrine effects which are suggested by the localization of their receptors on the maternal endometrium to regulate several ISG that aid in the complex communication between the maternal and fetal system (Johnson et al 2009). In one study, pig conceptus secretory proteins obtained from medium by culturing day 15 conceptuses for 30 hours were pooled and concentrated for intrauterine infusion and the results showed that these proteins had no antiluteolytic effect but they do, however, stimulate the secretion of PGE2 by uterine cells which is thought to enhance the structural integrity of the CL (Harney & Bazer 1989) Additionally, it has been reported that conceptus IFN are responsible for induction of endometrial FASLG, TNFSF10, and FAS expression on day 15 of pregnancy in the pig (Yoo et al 2020b). Furthermore, the same study showed that IFNG increases the expression of cysteine-X-cysteine chemokine ligands (CXCL) 9, 10, 11, and 12 which in turn, increase migration of T and NK cells, suggesting that IFN may play a role in recruitment of immune cells into the endometrium during the implantation period in pigs (Yoo et al 2020b).…”
Section: Conceptus Interferons In the Pigmentioning
confidence: 99%
“…In one study, pig conceptus secretory proteins obtained from medium by culturing day 15 conceptuses for 30 hours were pooled and concentrated for intrauterine infusion and the results showed that these proteins had no antiluteolytic effect but they do, however, stimulate the secretion of PGE2 by uterine cells which is thought to enhance the structural integrity of the CL (Harney & Bazer 1989) Additionally, it has been reported that conceptus IFN are responsible for induction of endometrial FASLG, TNFSF10, and FAS expression on day 15 of pregnancy in the pig (Yoo et al 2020b). Furthermore, the same study showed that IFNG increases the expression of cysteine-X-cysteine chemokine ligands (CXCL) 9, 10, 11, and 12 which in turn, increase migration of T and NK cells, suggesting that IFN may play a role in recruitment of immune cells into the endometrium during the implantation period in pigs (Yoo et al 2020b). While very little is known about conceptus interferons during early pregnancy in the pig, understanding their pathways could lead to more insight.…”
Section: Conceptus Interferons In the Pigmentioning
confidence: 99%
See 1 more Smart Citation